2004
DOI: 10.1128/aac.48.11.4084-4088.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Testing of Antimicrobial Activity of Bone Cement

Abstract: The purpose of this study was to establish a reliable and cost-effective microplate proliferation assay for in vitro antimicrobial testing of bone cement samples. Cement samples devoid of antimicrobial agents, loaded with 2% gentamicin or with different concentrations of high-porosity silver, were incubated in a 96-well microplate with several staphylococcal, Pseudomonas aeruginosa, and Enterococcus faecium isolates exhibiting different susceptibilities to gentamicin. After being rinsed, the samples were broug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 23 publications
3
34
1
1
Order By: Relevance
“…The presence of these indications of the peaks of amino acids supports the presence of proteins in cell-free filtrate as observed in UV-Vis spectra. It is well known that protein NPs interactions can occur either through free amine groups or cysteine residues in proteins and through the electrostatic attraction of negatively charged carboxylate groups in enzymes [40]. The two peaks observed at 1500 and 1255, 1/cm can be assigned to the C N stretching vibrations of the aromatic and aliphatic amines, respectively [41].…”
Section: Agnpsmentioning
confidence: 99%
“…The presence of these indications of the peaks of amino acids supports the presence of proteins in cell-free filtrate as observed in UV-Vis spectra. It is well known that protein NPs interactions can occur either through free amine groups or cysteine residues in proteins and through the electrostatic attraction of negatively charged carboxylate groups in enzymes [40]. The two peaks observed at 1500 and 1255, 1/cm can be assigned to the C N stretching vibrations of the aromatic and aliphatic amines, respectively [41].…”
Section: Agnpsmentioning
confidence: 99%
“…An extension orthosis of the knee is worn during ambulation. a b otic can be considered to be particular advantages of hand-made spacers (Alt et al 2004). They can be made in any surgical theater without specific tools.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the literature [27], the majority of Zn 2+ (1.5 ppm) and Ag + (0.2 ppm) release occurred in the first 24 hours. The literature reports a similar study using polymethylmethacrylate (PMMA) cement (VersaBond; Smith & Nephew, Memphis, TN, USA), where high absorbance rates, similar to those in the wells containing solely biofilm in this study, indicated that PMMA was unable to eliminate biofilm [28]. Therefore the reduction in absorbance in the wells that contained the novel Zn-Ag-GPC in this study indicates that the cement partially eliminated the biofilm present and prevented the formation of any more.…”
mentioning
confidence: 90%